Versification and syntax in Jeremiah 2-25 : syntactical constraints in Hebrew colometry - Cloete, Walter Theophilus Woldemar (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1987.